Komunikasi Virtual Antaranggota Kelompok Gamers Mobile Legend Poseidon - Yuditha Emmanuel, Ronald; Savitri Setyo Utami, Lusia (Kiwari, 2024)
Mobile Legend is an online game in the Moba genre or Multiplayer Online Battle Arena where each player has to work together to win the game. Roles are the roles of each hero in Mobile Legends which are grouped based on their duties and functions in a game. Communication is an important factor in this game because in the game you have to have a strategy that must be carried out together, therefore teamwork is needed. Usually in the Mobile Legend game virtual communication and group communication are the main choices for players so they can carry out the strategies that have been prepared. The purpose of this research is to determine and describe virtual communication between groups within the Poseidon team. This research was conducted using a qualitative approach using the case study method. Data was obtained from interviews with four informants, observation, documentation and literature study. The research results show that communication is the most important thing in playing the Mobile Legend game and choosing the communication media to be used also has a very important role for gamers so they can communicate comfortably virtually. A team must have a leader who is the main figure in directing the players and maintaining communication so that there is no miscommunication and differences of opinion between the team. Mobile Legend merupakan salah satu game online bergenre Moba atau Multiplayer Online Battle Arena di mana setiap pemain harus saling bekerja sama untuk memenangkan permainannya. Komunikasi menjadi faktor penting di dalam permainan ini karena dalam permainannya harus memiliki strategi yang harus dijalankan bersama, maka dari itu kerja sama tim diperlukan. Tujuan penelitian ini adalah untuk mendeskripsikan komunikasi virtual antaranggota kelompok di dalam tim Poseidon. Penelitian ini dilakukan dengan pendekatan kualitatif dengan metode studi kasus. Data diperoleh dari kegiatan wawancara dengan empat orang informan, observasi, dokumentasi, dan studi pustaka. Hasil penelitian menunjukkan bahwa komunikasi menjadi hal terpenting dalam bermain game Mobile Legend dan pemilihan media komunikasi yang akan digunakan juga memiliki peran yang sangat penting bagi para gamersagar dapat berkomunikasi virtual dengan nyaman. Di dalam sebuah tim harus memiliki seorang leader yang menjadi sosok utama dalam mengarahkan pemain dan menjaga komunikasi supaya tidak terjadi miskomunikasi dan perbedaan pendapat antartim.